2010
DOI: 10.1055/s-0030-1269853
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones Affect Plasma Ghrelin and Obestatin Levels

Abstract: Using radioimmunoassay, the effects of thyroid hormones on plasma total ghrelin (Gh) and obestatin (Ob) concentrations were evaluated in thyrotoxic patients with an excess of thyroid hormones and in hypothyroid patients lacking endogenous thyroid hormones. 24 patients with thyrotoxicosis, 25 hypothyroid patents after total thyreoidectomy performed due to thyroid cancer, and 17 control subjects were examined. Compared with the controls, the ghrelin and obestatin were elevated in hypothyroidism, while they were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
3
11
1
1
Order By: Relevance
“…The relationship between thyroid cancer pathogenesis and ghrelin and obestatin expression has not been clearly defined. Furthermore, since the function of thyroid gland is associated with the maintenance of energy balance, the relationship between ghrelin, obestatin and thyroid function is worthy of consideration [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between thyroid cancer pathogenesis and ghrelin and obestatin expression has not been clearly defined. Furthermore, since the function of thyroid gland is associated with the maintenance of energy balance, the relationship between ghrelin, obestatin and thyroid function is worthy of consideration [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…68 Both DAG and AG levels were found to be significantly lower in hyperthyroid patients, and plasma concentrations were reestablished after return to a euthyroid state. [69][70][71][72] In the same studies, ghrelin levels were correlated with insulin-resistance parameters. Also, the AG-induced stimulation of GH was blunted, while ACTH release was twofold higher in patients with hyperthyroidism versus healthy individuals.…”
Section: Ghrelin and Energy Metabolism Ghrelin And Thyroidmentioning
confidence: 83%
“…73,74 In contrast, higher total ghrelin levels are observed in patients with hypothyroidism. 70 In rats, central administration of AG daily for 5 days was shown to increase the weight of the pituitary and to reduce the size of TSH-immunopositive cells in the pituitary. 75 These effects were associated with a reduction of TSH and an increase in T 4 concentrations in the blood.…”
Section: Ghrelin and Energy Metabolism Ghrelin And Thyroidmentioning
confidence: 99%
“…Kosowicz et al [17], using radioimmunoassay, observed that ghrelin and obestatin were elevated in hypothyroidism, while decreased in thyrotoxicosis. The plasma ghrelin and obestatin levels differ depending on the thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…In thyroid hormone deficiency, plasma ghrelin and obestatin are increased, while in patients with excess of thyroid hormones, the levels are definitely lower. The ghrelin/obestatin ratio is higher in hypothyroidism than in the control subjects and thyrotoxic patients [17]. …”
Section: Discussionmentioning
confidence: 99%